Slovenska poezija v devetdesetih letih - Novak-Popov, Irena (Jezik in slovstvo, 2000)
The article discusses several noticeable shifts in the themes and subject matter of the generally very heterogeneous and rich Slovene poetry in the last decade. It notices signs of deep shifts in the appropriation of poetic traditions and re-evaluation of individual experiences, which is present both in the poets' responses to the unique conditions of the present day and in their establish connections with the spiritual universe and with the universe of the other.
Keywords: Slovene literature; slovenska književnost; slovenska poezija; 1990/2000; literarne študije